Language learning strategies of ESL students in online distance learning environment / Nur Alyani Khairol Anuar & Muhammad Irfan Mokhtar - Khairol Anuar, Nur Alyani; Mokhtar, Muhammad Irfan (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
This study reports on the use of Language Learning Strategies by L2 learners in online distance learning environment. When learning, learners will either consciously or unconsciously use language learning strategy (LLS) in order to process new information in their language lesson. In 1990, Oxford comes out with Strategies Inventory of Language Learning (SILL). This inventory has six broad categories: Cognitive, Memory, Affective, Meta- cognitive, Compensatory, and Social strategies. Various researches then have been conducted with their focus on LLS in L2 learning. LLS has been found to help learners to achieve better language achievement. While technology keeps on moving forward, it also lays its effects on teaching and learning process. The advent of technology gives L2 learners the opportunity to learn the language in technology-mediated environment. Thus, this study examined the preference of L2 learners in LLS when learning English in online distance environment. 78 respondents were involved in this study and questionnaires were given as the research instrument. Result shows that in term of LLS preference, learners used more Compensation strategy when learning English online. There is also a significant difference between male and female learners in term of LLS use. Female used more LLS as compared to male. Female learners preferred to use Metacognitive strategy, while male used Compensation strategy the most. The findings of this study have pedagogical impacts on English teaching and learning process.